Changes in the seroprevalence and risk factors between the first and second waves of COVID-19 in a metropolis in the Brazilian Amazon - da Silva Torres, Maria Karoliny; Lopes, Felipe Teixeira; de Lima, Aline Cecy Rocha; Cordeiro Lima, Carlos Neandro; dos Santos Brito, Wandrey Roberto; Gonçalves, Janete Silvana S.; dos Santos Oliveira, Onayane; de Oliveira Freitas, Vanessa; dos Santos, Bernardo Cintra; Santos de Sousa, Renata; Carvalho Gomes, Jayanne Lilian; Sarmento Botelho, Bruno José; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
In Brazil, the coronavirus disease 2019 (COVID-19) epidemic spread rapidly in a heterogeneous way, mainly due to the different socioeconomic and behavioral characteristics of different regional populations and different evaluation periods. We performed a cross-sectional study including 1,337 individuals (first wave = 736/second wave = 601) after the first two waves of COVID-19 in the city of Belém, the capital of the state of Pará. The detection of IgG anti-SARS-CoV-2 antibodies was performed using an enzyme-linked immunosorbent assay test followed by statistical analysis using the RStudio program. Our results showed an increase in the seroprevalence (first wave= 39.1%/second wave= 50.1%) of anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) IgG antibodies in the population of Belém from the first to the second pandemic wave. Advanced age, primary or secondary education level, lack of social isolation, and a low frequency of protective mask use were considered risk factors for SARS-CoV-2 infection during the first wave compared to the second wave. This study is one of the firsts to provide important information about the dynamics of virus circulation and the groups vulnerable to exposure in the two major periods. Our data emphasize the socioeconomic characteristics of the affected population and that nonpharmacological prevention measures are crucial for combating the pandemic.